Pancreatic Intraductal Papillary Mucinous Neoplasm Associated Colloid Carcinoma - Flor-de-Lima, B (2021)
Colloid carcinomas are rare pancreatic tumors characterized by the presence of mucin pools with scarce malignant cells. Most of these neoplasms arise from intestinal-type intraductal papillary mucinous neoplasms (IPMNs). We report a case of a 77-year-old male patient who presented with weight loss, asthenia, lumbar pain and diabetes. Imaging studies revealed a mixed-type IPMN with high-risk features and a possible invasive component. The patient underwent surgical resection and the histology confirmed an invasive colloid carcinoma of the pancreas associated with an intestinal-type IPMN. Although invasive ductal and colloid carcinomas may look similar on imaging studies, its distinction is important because the latter have a better prognosis.